Dampak Latihan Simple Circuit dan Running Circuit Terhadap Peningkatan Daya Tahan Kardiovaskular Dan Kelelahan - Cece Maulana; Hendra Rustiawan; Sri Maryati (Universitas Galuh, 2021)
This research aims to determine the simple circuit training method with running circuits to increase cardiovascular endurance and fatigue. The research method used was experimental. The research design used was a two-group pre-test-post-test design. The study was male students in the fourth semester of the 2019-2020 academic year. The sampling technique used was the stratified random sampling technique. The instruments used in this research were the multi-stage fitness test (MSFT) for the cardiovascular endurance test (vo2max) and the flamingo balance test for fatigue. Test data analysis using hypothesis testing, namely paired sample t-test. The results showed that increased cardiovascular endurance in the simple circuit training method was 2.06%; the percentage of increased cardiovascular endurance in the running circuit training method was 15.02%. While fatigue research results on the simple circuit method were 22.36%, the rate of increased fatigue in the running circuit training method was 9.58%. The conclusion is the simple circuit training method and running circuit have a significant effect on cardiovascular endurance, while the fatigue variable increases negatively. The author suggests that there should be further research on the duration of giving exercise in both training methods. The research results obtained are better.Metode latihan simple circuit dengan running circuit dalam penelitian ini bertujuan untuk mengetahui peningkatan daya tahan kardiovaskular dan kelelahan. Metode penelitian yang digunakan adalah eksperimen. Desain penelitian yang dugunakan adalah two-group pre-test-post-test design. Subjek dalam penelitian ini adalah mahasiswa putra tingkat empat semester genap tahaun ajaran 2019-2020.Teknik pengambilan sampel adalah teknik stratified random sampling. Instrument yang digunakan dalam penelitian ini adalah multi-stage fitness test (MSFT) untuk tes daya tahan kardiovaskular (vo2max) dan flamingo balance tes. Uji analisis data menggunakan uji hipotesis yaitu paired sample t-test. Hasil penelitian diperoleh persentase peningkatan daya tahan kardiovaskular pada metode latihan simple circuit sebesar 2.06%, Persentase peningkatan daya tahan kardiovaskular pada metode latihan running circuit sebesar 15.02%. Sedangkan hasil penelitian kelelahan pada metode simple circuit sebesar 22.36%, Persentase peningkatan kelelahan pada metode latihan running circuit sebesar 9.58%. Kesimpulannya adalah metode latihan simple circuit dan running circuit berpengaruh secara signifikan terhadap daya tahan kardiovaskular, sedangkan pada variabel kelelahan meningkat secara negatif. Penulis menyarankan agar adanya penelitian lanjutan bagian durasi pemberian latihan pada ke-dua metode latihan tersebut agar hasil penelitian yang didapatkan lebih baik.